Assessing the Harmonization Potential of Variable Speed Limit Systems. Issue 1 (2016) - Ackaah, Williams; Huber, Gerhard; Bogenberger, Klaus; Bertini, Robert L.
Variable speed limit (VSL) control systems have been used as a link control scheme on freeways and urban arterial roads. VSL systems aim to provide advance warning, to harmonize traffic speeds, or to accomplish both. The objective of this paper is to develop methods for assessing the harmonization potential of VSL systems. Two approaches based on the ability of the system to reduce inhomogeneity in the traffic stream and improve the consistency (proper coordination) of the displayed speed limits are presented. Inhomogeneity in the traffic stream was checked by first identifying the traffic state and assessing the ability of the system to reduce the speed differential in the metastable traffic state (i.e., flows > free flow but with speeds > congestion speed). The coefficient of variation was used to quantify the standard deviation of speed. Consistency was assessed by observing the consecutive dynamic changes in the displayed speed limits as drivers traverse the route. This assessment was done by reconstructing the traffic state from loop detector data, generating virtual trajectories based on the reconstruction, and finally tracking the virtual vehicles to reproduce the sequence of speed limits that drivers would have experienced. The methods developed were tested for the VSL system on the Autobahn 99 near Munich, Germany.